The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c4sm01496k
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of poly(N-isopropylacrylamide)–nucleobase supramolecular complexes featuring bio-multiple hydrogen bonds

Abstract: In this study we employed poly(N-isopropylacrylamide) (PNIPAAm) as a matrix that we hybridized with five different nucleobase units (adenine, thymine, uracil, guanine, cytosine) to generate PNIPAAm-nucleobase supramolecular complexes (PNSCs) stabilized through bio-multiple hydrogen bonds (BMHBs). These nucleobase units interacted with PNIPAAm through BMHBs of various strengths, leading to competition between the BMHBs and the intramolecular hydrogen bonds (HBs) of PNIPAAm. The changes in morphology, crystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…In the spectrum of NG0, the absorption band around 3464 cm −1 became broader, indicating hydrogen bond formation between the –OH and –NHCO groups. Moreover, the bands at 1670 and 1597 cm −1 in the spectrum of PNIPAAm shifted to 1658 and 1558 cm −1 , respectively, in the spectrum of NG0, indicating hydrogen bonding interactions between bovine skin gelatin and PNIPAAm [ 39 ]. This information proved that PNIPAAm and bovine skin gelatin were highly miscible with each other.…”
Section: Resultsmentioning
confidence: 99%
“…In the spectrum of NG0, the absorption band around 3464 cm −1 became broader, indicating hydrogen bond formation between the –OH and –NHCO groups. Moreover, the bands at 1670 and 1597 cm −1 in the spectrum of PNIPAAm shifted to 1658 and 1558 cm −1 , respectively, in the spectrum of NG0, indicating hydrogen bonding interactions between bovine skin gelatin and PNIPAAm [ 39 ]. This information proved that PNIPAAm and bovine skin gelatin were highly miscible with each other.…”
Section: Resultsmentioning
confidence: 99%
“…f Roughness (Ra) was obtained from AFM. BMHBs can improve H + transport in PNIPAAm-b-ssDNA copolymer brushes, 18,19 so we focused mainly on determining the temperature-responsive resistance of our functionalized surfaces. The linear I-V curves exhibited ohmic behavior at 25 and 80 C during device use (Scheme 2).…”
Section: Pnipaam-b-ssdna Copolymer Brushes For Label-free Target Dna mentioning
confidence: 99%
“…17 Researchers have also shown that DNA block copolymers can be assembled into various morphologies by utilizing the molecular recognition property of DNA. 18,19 Gianneschi and co-workers synthesized a DNA brush copolymer that undergoes a reversible sphere-to-cylinder morphology change by DNA cleavage and hybridization. 20 Herrmann et al reported the formation of rodlike assemblies of DNA-block-poly(propylene oxide) (DNA-b-PPO) using a long repetitive complementary DNA strand as a template.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Recently, self-assembly conjugation in polymer chemistry has become increasingly prominent in the produc-tion of smart materials due to its advantage of being stimuliresponsive with reversible interactions. [16,17] In our previous work, purine derivatives that had a tetrazole ring showed DNA damage and higher antibacterial activities compared to cyano compounds. [18] Tetrazoles, a well-described class of nitrogen-containing heterocycles, have shown valuable properties with a wide range of applications in materials science and beyond, including catalysis, propellants, information recording systems, explosives, and with possible applications in high-energy chemistry.…”
Section: Introductionmentioning
confidence: 98%